Characterisation of low crystallinity CNTs incorporated zinc silicate ceramic composites: morphology, optical, dielectric and microhardness properties - Chan, Kar Fei; Mamat, Md Shuhazlly; Mohd Zaid, Mohd Hafiz; Tanemura, Masaki; Mohd Yusop, Mohd Zamri; Maruyama, Takahiro; Sharma, Kamal Prasad; Liza, Shahira; Yaakob, Yazid (Springer Science and Business Media Deutschland GmbH, 2026)
Carbon nanotubes has been researched deeply as a reinforced material, since it showed good properties in different matrices, yet the aggregation issue has always been brought up to restrain its applicability. Carbon nanotubes’ rapid electronic conductivity was expected to enhance the ceramic composite specifically zinc silicate as the potential candidate of the fluorescent materials. In this study, low crystallinity carbon nanotubes (CNTs) synthesized by chemical vapor deposition were mixed with zinc silicate made by melt-quenching to fabricate the CNTs incorporated zinc silicate composites. The composites were analyzed using Raman, XPS, FESEM, UV-Vis, LCR and Vicker’s microhardness tester. It was found that the optical bandgap energy of the CNTs added composites a decay in the optical bandgap while the luminescence behavior remains unchanged. The FESEM image revealed that the composite included CNTs pullout and aggregation. LCR analysis showed that ZS/CNT-x composites have a higher AC conductivity value, together retain their non-ohmic conductivity with the unchanged molecular structure. Through this study, the results allowed the CNTs ceramic research path to be served the scientific community in the development of narrow bandgap material with the wide bandgap compound as the starting material.